Tumor and stroma COL8A1 secretion induces autocrine and paracrine progression signaling in pancreatic ductal adenocarcinoma - Yan, Bin; Liu, Li; Zhao, Lian; Hinz, Ulf; Luo, Yiqiao; An, Xuefeng; Gladkich, Jury; Torre, Carolina de la; Huang, Zhenhua; Schrapel, Daniel; Gross, Wolfgang; Fortunato, Franco; et al. (Matrix biology, 2022)
Several collagen subtypes are involved in pancreatic ductal adenocarcinoma (PDAC) desmoplasia, which constrains therapeutic efficacy. We evaluated collagen type VIII alpha 1 chain (COL8A1), whose function in PDAC is currently unknown. We identified COL8A1 expression in 7 examined PDAC cell lines by microarray analysis, western blotting, and RT‒qPCR. Higher COL8A1 expression occurred in 2 gemcitabine-resistant PDAC cell lines; pancreas tissue (n=15) from LSL-KrasG12D/+; p48-Cre mice with advanced PDAC predisposition; and PDAC parenchyma and stroma of a patient tissue microarray (n=82). Bioinformatic analysis confirmed higher COL8A1 expression in PDAC patient tissue available from TCGA (n=183), GTEx (n=167), and GEO (n=261) databases. siRNA or lentiviral sh-mediated COL8A1 inhibition in PDAC cells reduced migration, invasion and gemcitabine resistance and resulted in lower cytidine deaminase and thymidine kinase 2 expression and was rescued by COL8A1-secreting cancer-associated fibroblasts (CAFs). The activation of COL8A1 expression involved cJun/AP-1, as demonstrated by CHIP assay and siRNA inhibition. Downstream of COL8A1, activation of ITGB1 and DDR1 receptors and PI3K/AKT and NF-κB signaling occurred, as detected by expression, adhesion and EMSA binding studies. Orthotopic transplantation of PDAC cells with downregulated COL8A1 expression resulted in reduced tumor xenograft growth and lower gemcitabine resistance but was prevented by cotransplantation of COL8A1-secreting CAFs. Most importantly, COL8A1 expression in PDAC patient tissues from our clinic (n=84) correlated with clinicopathological data, and we confirmed these findings by the use of patient data (n=177) from the TCGA database. These findings highlight COL8A1 expression in tumor and stromal cells as a new biomarker for PDAC progression.